Russian monetary policy: Assessing the track record - Claudia M. Buch (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
Since early 1995, monetary stabilization has gradually been achieved in Russia. Extremely high real interest rate have been maintained throughout autumn 1996, an exchange rate target has been adhered to since mid-1995, auctions of Central Bank credit have gained in importance, and subsidized lending has been cut down. However, the conduct of monetary policy remains a trial-and-error process: Indirect budget financing through the CBR still occurs, the fixed exchange rate regime has caused a lack of control over the monetary base, and the money multiplier is relatively unstable. Preliminary empirical evidence shows that money demand has remained relatively stable since the beginning of reforms. Still, short-run fluctuations of money demand are substantial, and further portfolio adjustments are likely if inflationary expectations decline and if the capital account becomes more open. The success of monetary stabilization crucially depends on the effectiveness with which the CBR can defend its independence. Because financial sector stability is an important condition for a predictable and stable monetary policy, further measures to restructure and to consolidate the banking sector need to be pursued in parallel to structural reforms of the Russian economy.
Keywords: E5; P42; 330; monetary policy; central banking and the supply of money and credit; planning; coordination; and reform; Russia; Geldpolitik; Übergangswirtschaft; Geldangebot; Geldnachfrage; Russland